Dye Laser Applications in Cosmetic Dermatology: Efficacy and Safety in Treating Vascular Lesions and Scars - Alessandro Clementi; Giovanni Cannarozzo; Simone Amato; Elena Zappia; Luigi Bennardo; Simone Michelini; Cristiano Morini; Mario Sannino; Caterina Longo; Steven Paul Nistico (Cosmetics)
Cosmetic dermatology increasingly utilizes laser technologies to address various aesthetic concerns. This study evaluates the efficacy of the flash-lamp pulsed-dye laser (FPDL) in treating vascular and scar-related conditions. A cohort of 71 patients with diverse vascular lesions, including facial telangiectasia, port-wine stains (PWSs), striae rubrae, erythematous acne scars, facial traumatic scars, and keloids, was treated using the FPDL (Synchro Vas-Q, Deka MELA). Treatment protocols varied based on lesion type, with sessions ranging from one to eight at intervals of four to eight weeks. Clinical outcomes were assessed using a four-point grading scale and patient satisfaction surveys. Results indicated that 70.4% of patients achieved excellent clearance of lesions, while 16.9% and 9.9% showed moderate-good and slight clearance, respectively. Minimal or no improvement was observed in 2.8% of cases. High patient satisfaction was reported, correlating with effective lesion reduction and manageable side effects, primarily post-operative purpura. The study underscores FPDL’s selective efficacy for hemoglobin-rich lesions and its safety profile, advocating for its continued use in cosmetic dermatological practices. These findings contribute to the growing evidence supporting laser therapy as a pivotal tool in aesthetic medicine, emphasizing the importance of tailored treatment protocols and patient education for optimal outcomes.